The Association of Renal Agenesis and Ipsilateral Seminal Vesicle Cyst: Zinner Syndrome Case Report. (23rd June 2019) - AlArifi, Mishal; Al-Gahwary, Magdi; Gomha, Mohamed
Abstract : Introduction . Zinner syndrome is a rare congenital malformation characterized by the association of an ipsilateral renal agenesis, ipsilateral seminal vesicle cyst, and ipsilateral ejaculatory duct obstruction. This case is one of the first to be reported in the Kingdom of Saudi Arabia. Case Presentation . A 20-year-old Saudi male patient presented complaining of chronic left groin pain radiating to the left testis and the medial aspect of the left thigh for the last 6 years. Patient is also complaining of painful ejaculation with no history of lower urinary tract symptoms, hematuria, or trauma. Physical examination was unremarkable. Ultrasound (US) report from the referring hospital mentioned that there is a left pelvic mass. Computed tomography (CT) and magnetic resonance imaging (MRI) showed diffuse distension of left seminal vesicle (9 X 7 cm) cyst with ipsilateral left renal agenesis which corresponds to Zinner syndrome. Left seminal vesicle cyst excision through a low midline incision was done. The patient was asymptomatic during his follow-up in our clinic with disappearance of the pain. Conclusion . The combination of a good clinical history and radiological assays aided in making the diagnosis. Surgical intervention is the mainstay in the management plan in symptomatic patients.